Multiple drug delivery hydrogel system for spinal cord injury repair strategies - Perale, Giuseppe; Rossi, Filippo; Santoro, Marco; Peviani, Marco; Papa, Simonetta; Llupi, Dorina; Torriani, Paola; Micotti, Edoardo; Previdi, Sara; Cervo, Luigi; Sundstrom, Erik; Boccaccini, Aldo R.; et al. (Journal of Controlled Release, 2012)
The multifactorial pathological progress of spinal cord injury (SCI) is probably the main reason behind the absence of efficient therapeutic approaches. Hence, very recent highlights suggest the use of new multidrug delivery systems capable of local controlled release of therapeutic agents. In this work, a biocompatible hydrogel-based system was developed as multiple drug delivery tool, specifically designed for SCI repair strategies. Multiple release profiles were achieved by loading gel with a combination of low and high steric hindrance molecules. In vitro, in vivo and ex vivo release studies showed an independent combination of fast diffusion-controlled kinetics for smaller molecules together with slow diffusion-controlled kinetics for bigger ones. A preserved functionality of loaded substances was always achieved, confirming the absence of any chemical stable interactions between gel matrix and loaded molecules. Moreover, the relevant effect of the cerebrospinal fluid flux dynamics on the drug diffusion in the spinal cord tissue was here revealed for the first time: an oriented delivery of the released molecules in the spinal cord tract caudally to the gel site is demonstrated, thus suggesting a more efficient gel positioning rostrally to the lesion. © 2011 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.multip
Keywords: Drug release; Hydrogel; Polymer; Spinal cord injury